Rhizobium fredii and Rhizobium meliloti produce 3-deoxy-D-manno-2-octulosonic acid-containing polysaccharides that are structurally analogous to group II K antigens (capsular polysaccharides) found in Escherichia coli. - Reuhs, B L (1993)
The polysaccharide components from cultured cells of Rhizobium fredii USDA205 and Rhizobium meliloti AK631 were extracted with hot phenol-water and separated by repetitive gel filtration chromatography. Polyacrylamide gel electrophoresis, nuclear magnetic resonance spectrometry, and gas chromatography analyses showed that both of these bacterial species produce unique polysaccharides that contain a high proportion of 3-deoxy-D-manno-2-octulosonic acid (Kdo). These polysaccharides, which constituted a major portion of the extracted carbohydrate, are not excreted into the growth media (i.e., they are not extracellular polysaccharides) and are structurally distinct from the lipopolysaccharides. The primary structure of the preponderant polysaccharide from R. fredii USDA205 was determined by high-performance anion-exchange liquid chromatography, nuclear magnetic resonance spectrometry, fast atom bombardment-mass spectrometry, and gas chromatography-mass spectrometry; it consists of repeating units of [-->3)-alpha-D-Galp-(1-->5)-beta-D-Kdop-(2-->]n. This molecule is structurally analogous to the constituents of one subgroup of K antigens (capsular polysaccharides) produced by Escherichia coli. Polysaccharides of this type have not previously been identified as components of rhizobial cells. The Kdo-containing polysaccharide from R. meliloti, which has not been completely characterized, appears to be structurally related to that of R. fredii.